Trichuris dysentery syndrome, the neglected tropical disease: a case series - Yulia Fatma Wardani; Ida Safitri Laksono; Teti Adriana Lubis (Paediatrica Indonesiana, 2022)
Almost 2 billion people, about a quarter of the world’s population, are infected with soil-transmitted helminths (STH) worldwide. Approximately 270 million preschool children and more than 550 million school-age children live in areas of extensive parasite transmission.1,2 Indonesia is a moderate-to-high-risk area of STH, with an overall mean prevalence of 28.12%. However, the prevalence in Papua is higher.3 A study reported that 50% of school-aged children in Jayapura, Papua, a high-risk area, suffered from STH, with distributions of 48.5% Ascaris lumbricoides, 28.6% Trichuris trichiura, 14.3% hookworm, and 8.6% mixed infection.4